Levonorgestrel Releasing Intrauterine System in the Treatment of Dysfunctional Uterine Bleeding - Begum, Rokeya; Khanam, Mafruha (Medicine Today, 2014)
This study was designed to determine progress of women presenting with dysfunctional uterine bleeding (i.e decrease in amount and duration of bleeding in days) due to a cause amenable to treatment. To evaluate improvement in Haemoglobin level (Hb gm%) in patients during treatment. The study was conducted in the Department of Obstetrics & Gynaecology, Chittagong Medical College Hospital, Chittagong, Bangladesh from August 2008 to July 2010. Thirty six patients with Dysfunctional Uterine Bleeding (DUB) in 30-45 years age group with Body Mass Index (BMI) 0f 18-30 during treatment period were included in the study. They were counselled, investigated and had Levonogestrel Intrauterine device inserted. Outcome was measured by Hb improvement and decrease in blood loss both in amount and duration. Record was kept and follow up was done. Ninety percent of the patients were relieved from menorrhagia and one hundred percent improvement was seen in cases with polymenorrhagia. 50% patients had an Hb of >11.1gm% after 3 months of use. Levonogestrel intrauterine system or LNG-IUS is a safe and effective device for the treatment of DUB patients and it is an alternative to hysterectomy. DOI: http://dx.doi.org/10.3329/medtoday.v25i2.17921 Medicine Today 2013 Vol.25(2): 60-62